Academic writing strategies among Danish students with a professional background - Karin Højbjerg; Anette Lykke Hindhede (Education Inquiry, 2023)
ABSTRACTExpectations of how theory, empirical material, and methods should be dealt with in academic writing has not always been explicitly communicated to students. Due to a heterogeneity in student populations enrolled in higher degree courses worldwide, diversity in academic writing practices has increased. This paper explores academic writing practices among a group of students with professional, vocational backgrounds and close relationships to practical knowledge. Twelve examination papers from fifteen students within a continuing education program at a Danish university have been analysed inspired by Aristotle’s activities of theoria and praxis and Bourdieu’s concept of strategy. In this perspective, the study shows student strategies of how the students seem to retain an affinity to allow a practical approach of social and ethical evaluation when handling theory, empirical material, and methods. The analysis shows that students’ personal preferences are brought into the foreground.